Implementation of The Shortest Route Value Calculation Using The Generate and Test Algorithm - Andri Yunaldi (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
Search and tracking issues are important in determining the success of a system based on Artificial Intelligence. One that is well known is the Generate and Test method which is one of several heuristic search models in Artificial Intelligence terminology. Generate and Test is an algorithm that performs tests to find the shortest route in the case of a trip. Generete and test is suitable for measuring the smallest distance. The benefit of this research is to save time and money in traveling the distance to a city. How it works in this algorithm is to see the initial state as a star point and see the final state as a goal state. Perform all calculations to each distance provided that it starts from the initial strat and ends with the end strat. Count all values, choose the smallest value to reach the Final goal. If the search results have been found then the search is stopped, if not the solution then the search continues until it finds the smallest result to find a solution.